MODEL SISTEM ANTRIAN PADA PELAYANAN RESTORAN CEPAT SAJI (Studi Kasus di KFC Gajah Mada Kabupaten Jember) - Bambang Herry Purnomo; Bertung Suryadharma; Nurma Yunita Ekasari (JURNAL AGROTEKNOLOGI, 2021)
KFC is one of the fast food restaurants in the Jember Regency which is never deserted of visitors, especially that on Gajah Mada Street. The purposes of this study were to determine the characteristics of the queuing system, analyze the queuing applied at KFC, formulate recommendations for improving the queuing system to reduce queuing, and minimize costs. The Data analysis was performed to compare manual calculations and simulation methods using ARENA 14.0. The characteristics of the current queue at KFC are random and unlimited arrival patterns, FIFO (first in first out) queue discipline, and the design of the single phase multi channel queuing system. The queuing distribution used for arrival and service time was the exponential distribution. The queuing model notation at the M/M/2 cashier: FIFO/∞/∞. The recommended queuing model that can be applied was to add 1 cashier to 3 cashiers at a cost of Rp 150,560 from the scenario made. The performance variable in the scenario becomes less than the initial condition, which was ρ cashier becomes 188%, total Wq about 0.92 minutes, and Lq about 2 people. Adding these facilities changes the queuing model notation to (M/M/3: FIFO/∞/∞). Keywords: ARENA, FIFO queuing discipline KFC Jember, queuing system